BASIC CONCEPT FOR DEVELPOMENT OF RURAL TOURISM - Mihajlovski, Goran; Bojkovska, Katerina; Jankulovski, Nikolche (Horizons - International Scientific Journal, 2021)
The need for rapid economic development leads to the creation of a new concept of the consumer market. It is actually a concept that offers something new to consumers in terms of a new product or new service, in this case a better offer in the field of rural tourism. Namely, for the development of a basic concept of rural tourism, it is necessary for it to be developed in an environment that has rich traditions, natural resources, cultural values and individual authenticity. Based on that, the basic concept for development of rural tourism is based on setting a framework for its development and its identification as a model for better local economic development. In fact, the purpose of this paper is to present a basic concept for the development of rural tourism in order to improve the quality of life of the population of these areas.